Moringa Oleifera: an alternative ingredient to improve the egg quality of Japanese quail - Garcia, R.g.; Gandra, E.r.s.; Burbarelli, M.f.c.; Valentim, J.k.; Felix, G.a.; Lopes, B.a.; Bacha, F.b.; Melo, C.m.f. [UNESP]; Silva, J.p.; Komiyama, C.m.; Caldara, F.r. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2021)
This study aims to evaluate effects of inclusion of moringa in Japanese quail diets on laying performance, egg quality, blood parameters, serum biochemical profile, and behavior. One hundred and forty-four Japanese quails, approximately 35-d-old, were distributed in a completely randomized design with four treatments and six replications. Treatments were diet inclusion of 0, 2, 4 and 6% of dried and ground moringa leaves. The inclusion of moringa in diets reduces the quadratic feed intake up to the level of 1.20%, increases weight of eggs with a quadratic behavior up to 3.80%, and linearly increases yolk weight. Yolk color changes with higher levels of inclusion of moringa and resulted in more intense colors. The biochemical profile of quails changed slightly but remains within the normal range. The inclusion of 4% of moringa in diets increases alkaline phosphatase. Regarding cholesterol and triglycerides, diet with 6% moringa inclusion was lower when compared to the others. The behavior of laying quails does not change due to inclusion of moringa in diets. Up to 3.83% of Moringa oleifera can be included in Japanese quail diet to improve egg quality without compromising performance, biochemical profile, blood parameters and behavior.

O objetivo deste estudo foi avaliar a inclusão de Moringa oleifera na dieta de codornas japonesas sobre o desempenho, a qualidade de ovos, os parâmetros sanguíneos, o perfil bioquímico e o comportamento. Foram utilizadas 144 codornas japonesas, com aproximadamente 35 dias de idade, as quais foram distribuídas em delineamento inteiramente ao acaso, com quatro tratamentos e seis repetições cada. Foram fornecidas dietas com 0, 2, 4 e 6% de folhas desidratadas e moídas de moringa. A inclusão de moringa nas dietas reduziu quadraticamente o consumo até o nível de 1,2%, aumentou o peso dos ovos com comportamento quadrático até o nível de 3,8% e aumentou linearmente o peso da gema. A coloração da gema se intensificou com maiores inclusões de moringa. O perfil bioquímico sofreu alterações leves, mas não saiu dos padrões normais para codornas. A inclusão de 4% de moringa nas dietas aumentou os níveis de fosfatase alcalina. Já a inclusão de 6% reduziu níveis de colesterol e triglicérides. O comportamento das codornas não se alterou com a inclusão de moringa nas dietas. A inclusão de até 3,83% de Moringa oleifera na dieta de codornas japonesas aumenta a qualidade de ovos sem comprometer o desempenho, o perfil bioquímico, os parâmetros sanguíneos e o comportamento delas.
[Moringa oleifera: um ingrediente alternativo na melhora da qualidade de ovos de codornas japonesas]
Keywords: antioxidants; egg quality; laying quails; medicinal plants; phytogenic additives; aditivos fitogênicos; antioxidantes; codornas de postura; plantas medicinais; qualidade de ovos